AKTIVITAS ANTIBAKTERI FORMULA OPTIMUM KRIM ANTIACNE FRAKSI ETIL ASETAT EKSTRAK DAUN TEH HIJAU (Camelia sinensis L) - Naniek Widyaningrum; Achmad Fudholi; Sudarsono Sudarsono; Erna P. Setyowati (Jurnal Ilmu Farmasi dan Farmasi Klinik, 2017)
ABSTRACT Green tea (Camellia sinensis L) contains EGCG, which has antibacterial activity. Stability, optimal concentration and formulation development has been observed before. This study aimed to determine the antibacterial effect stability of the ethyl acetate fractions of green tea leaves extract cream optimum formula and ethyl acetate fraction of green tea leaves extract (EAFGTLE 6%) against acne-causing bacteria, S. epidermidis. Anti-bacterial activity performed with diffusion assay method on S. epidermidis ATCC 35984 growths. The stability of anti-bacterial activity obtains during three months. The result analyzed using paired sample t-test (p: 0.95). The result showed there was no significant difference between EAFGTLE 6% inhibition ability (p=0.081) or even cream dosage optimum formula (p=0.079) during three months. It can be concluded that EAFGTLE 6% and optimum formula cream could inhibit its effectiveness during three months. Key words: Antibacterial activity, cream, ethyl acetate fraction, green tea leaves extract